Neuroprotective effects of ellorarxine in neuronal models of degeneration - Kouchmeshky, Azita; Whiting, Andrew; McCaffery, Peter (Frontiers in Neuroscience, 2024)
Introduction Retinoic acid (RA) was first recognised to be important for the central nervous system (CNS) in its developmental regulatory role and, given this action, it has been proposed in the adult CNS to regulate plasticity and promote regeneration. These types of roles have included support of neurogenesis, induction of neurite outgrowth, and protection from neuronal death. These functions are predominantly mediated by the retinoic acid receptor (RAR) transcription factor, and hence agonists for the RARs have been tested in a variety of models of neurodegeneration. This present study employs several in vitro models less explored for the action of RAR agonists to reverse neurodegeneration. Methods A series of assays are used in which neuronal cells are placed under the types of stress that have been linked to neurodegeneration, in particular amyotrophic lateral sclerosis (ALS), and the neuroprotective influence of a new potent agonist for RAR, ellorarxine, is tested out. In these assays, neuronal cells were subjected to excitotoxic stress induced by glutamate, proteostasis disruption caused by epoxomicin, and oxidative stress leading to stress granule formation triggered by sodium arsenite. Results Ellorarxine effectively reversed neuronal death in excitotoxic and proteostasis disruption assays and mitigated stress granule formation induced by sodium arsenite. This study also highlights for the first time the novel observation of RAR modulation of stress granules, although it is unknown whether this change in stress granules will be neuroprotective or potentially regenerative. Furthermore, the distribution of RAR agonists following intraperitoneal injection was assessed in mice, revealing preferential accumulation in the central nervous system, particularly in the spinal cord, compared to the liver. Gene expression studies in the spinal cord demonstrated that ellorarxine induces transcriptional changes at a low dose (0.01 mg/kg). Discussion These findings underscore the therapeutic potential of RAR agonists, such as ellorarxine, for ALS and potentially other neurodegenerative diseases.